La comunicación organizacional y su incidencia en el desempeño laboral de los colaboradores de la empresa M & Calera Santa S.A.C. - Huamachuco 2017 - Arana Sandoval, Olinda Nereyda (2018)
The development of this research work was developed in the company M & Calera Santa SAC, which groups various establishments, which are located in sectors distant from each other, but concentrated in the province of Sánchez Carrión, so the work of Research focuses on organizational communication and how it affects the work performance of its employees. The non-experimental, cross-sectional and correlational and descriptive type of research, the Inductive-Deductive Method, the Hypothetical-Deductive Method and the Analysis-Synthesis Method were used, the survey was also used as a research technique, the Cronbach's Alpha method yielded as a result for the Organizational Communication variable, an Alpha of 0.705, and for the variable of work performance, an Alpha of 0.861 that shows the reliability of the data obtained. For the development of this research work, the population is made up of 160 employees of the M & Calera Santa S.A.C. which is located in the province of Sánchez Carrión, who after being statistically processed a representative sample of 78 collaborators was determined, the instrument of data collection was applied, with the purpose of determining the impact of the organizational communication and its incidence in the performance of the collaborators, finding that there is a positive correlation of 0.83, which shows the existence that organizational communication has a positive impact on job performance.